(untitled) (Research, Society and Development, 2025)
This literature review sought to gather scientific papers from systematic reviews and clinical studies in humans, with the aim of improving understanding and obtaining a more objective assessment of the advantages of the technique. This study was carried out after a bibliographic review between the years 2016 and 2024, through the research platforms pubmed, scielo and google scholar. The articles were selected mainly with systematic review studies and clinical trials. In the first phase of treatment, the implantologist prepares the bone pocket (osteotomy) where the implant will be installed. The osseodensification (OD) technique is a non-extractive milling method because the bone is condensaded in the bone pocket of the preparation. The conventional osteotomy (SD) technique is considered extractive because it removes local bone to insert the implant. Differents drills are used throughout the surgical procedure. When used with methodology and practice, the (OD) technique can improve the osseointegration of dental implants in situations where there is little available bone. It promotes the expansion of the bone crest and improves the healing process due to the preservation of bone tissue at the preparation site.